2022
DOI: 10.1007/s11695-021-05867-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Overweight and Obesity in Male Adolescents: Prevalence, Socioeconomic Status, and Impact on Cardiovascular Risk in a Central European Country

Abstract: Background Obesity is one of the most important health-related problems of the twenty-first century. Data on its prevalence in Austria remain scarce. Aim of this study was to determine current trends of overweight and obesity, associated comorbidities and socioeconomic status in all 18-year-old male Austrian citizens, and its potential impact on the demand for bariatric surgery in the future. Methods Data from compulsory military conscription examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Our study found that the hazards of the obesity increased with father’s occupational position in early life, participants’ occupational position and educational attainment in adult life. Higher SESs in developed countries generally had lower hazards of obesity(9, 22), but this pattern does not apply to China. Low SES limited the opportunities available for excess to food consumption and increases physical labor, while high SES increased access to excess food and avoids physical labor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our study found that the hazards of the obesity increased with father’s occupational position in early life, participants’ occupational position and educational attainment in adult life. Higher SESs in developed countries generally had lower hazards of obesity(9, 22), but this pattern does not apply to China. Low SES limited the opportunities available for excess to food consumption and increases physical labor, while high SES increased access to excess food and avoids physical labor.…”
Section: Discussionmentioning
confidence: 92%
“…The bulk of evidences show that socioeconomic status (SES), such as education, occupation and income, very often lead to social differences in the prevalence of obesity and overweight (6,7). The majority of studies from western countries find an inverse relationship between SES and obesity (8,9). In the developing countries, this interrelationship shows a strong positive correlation between those.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concept of LTAD must be declined and calibrated in order to provide guidelines for technical staff: this clarification is necessary when considering the declining trends in physical fitness (Sandercock & Cohen, 2019), physical activity (Colella & D'Arando, 2021;Invernizzi et al, 2022;Tremblay et al, 2016) and motor skill development (Lawson et al, 2021;Bolger et al, 2019), alongside increased overweight and obesity prevalence (Gensthaler et al, 2022;Ogden et al, 2016) within youth populations.…”
Section: Discussion: Is It Possible To Think Of Alternative Models In...mentioning
confidence: 99%
“…NAFLD development is influenced by dysbiosis caused by obesity [ 50 ]. Obesity remains a major public health problem in Western societies, where its prevalence has increased considerably in recent years [ 51 , 52 ]. The main causes that contribute to the spread of obesity are thought to be sedentary lifestyles and excessive food intake [ 53 , 54 ], which induce a state of nutritional imbalance, especially in genetically predisposed individuals [ 53 , 54 ].…”
Section: Gut Microbiome Dysbiosis In Nafld and Obesitymentioning
confidence: 99%